A tutela de urgência no novo CPC: avanços e retrocessos - Sanches Junior, Antonio Roberto (2018)
This paper proposes to study the way taken by the guardianship of urgency in Brazilian law, from the Portuguese Ordinances to the 2015 CPC. It also undertakes research with the purpose of demonstrating the origin and evolution of urgent protection in foreign law, specifically in the legal orders from which the Brazilian guardianship of urgency was derived (Italian, French and Portuguese), with the purpose of discovering if the Brazilian legal order remained parallel or distanced from its origins. The first chapter describes the evolution of the protection of the guardianship of urgency in the national legal order, by means of the comparison of the legislative texts that were in force until the advent of CPC of 1939. The second chapter lends itself to studying the guardianship of urgency in the CPC of 1973, initially represented only by the precautionary process and by some special procedures (v.g. possessory injunction), being, from 1994, inserted the anticipation of guardianship for the common procedure. The third chapter is devoted to reporting the guardianship of urgency in the foreign law that, according to the doctrine, influenced the Brazilian, in order to demonstrate (at the end of the work) whether there has been a parallel evolution of the systems or if the systems have distanced. The fourth chapter lends itself to the investigation of the main exponents of both foreign law and national law, with regard to guardianship of urgency, adopting as a methodological proposal the separation of authors into two groups, taking into account that they had written before (when everyone were dedicated only to the study of precautionary measures) or after Law 8.952/94, which introduced the anticipation of guardianship in the Brazilian CPC (when they went to the study of anticipation of guardianship and its comparison with the system called precautionary). The fifth chapter lends itself to the study of the CPC of 2015 since the draft, through legislative discussions and culminating in the enacted text, as well are inquired controversial issues about the system of "temporary" guardianship of urgency in the manner in which it is promulgated, based on a unitary concept of precautionary guardianship of urgency, which includes conservative and satisfying techniques. The sixth chapter proposes a new approach to the guardianship of urgency system, from a new concept of guardianship precautionary/urgency, with possible changes de lege lata and suggestions de lege ferenda, in order to make the institutes more effective, in the light of its constitutional mission: provide justice promptly or, where this is not possible, prevent events from rendering ineffective the future judgment of merit